Synthesis and Biosynthesis of Mimosine - Notation, Albert David (My University, 1963)
DL-Mimosine has been synthesized by debenzylation and detosylation of the product obtained by condensation of 3-benzyloxy-4-pyrone with β-amino-α-tosylaminopropionic acid. A new method for the isolation of mimosine from Leucaena glauca Benth. is described. The biosynthesis of mimosine was studied by feeding radioactive aspartates, glycerol, glycerate and ribose to Mimosa pudica L. . Mimosine-C^14 was isolated and partially degraded, and it was shown that the carbon-3 of aspartic acid is specifically incorporated into the pyridone ring.
Keywords: synthesis, biosynthesis, Mimosine, debenzylation, aspartic acid